АЎЫЛ ХОЖАЛЫҒЫНЫҢ БАСЛЫ ЗЫЯНКЕСИ - ЖАЛПАҚ ТИСЛИ КРЫСА (NESOKIYA INDICA GRAY) МЕНЕН ГҮРЕС УСЫЛЛАРЫ - Палўанова, Г.Ж. (FAN va JAMIYAT, 2022)
The article provides information on how to combat small rodents, the most common pests of agriculture, milk thistle - the rattlesnake and prevent large-scale economic damage. One of the main methods of struggle is the selection and application of a method that gives a concrete and clear entrance to the rescue of ten damaged objects from the rat by the method of harmless struggle.